New Jersey Cemeteries and Tombstones : History in the Landscape - Veit, Richard F., 1968- (Book collections on Project MUSE., 2008)
In this sweeping tour of New Jersey's burial sites from the seventeenth century through the dawn of the twenty-first, readers will discover how headstones are much more than place markers for the deceased. From the earliest memorials that were once used by Native Americans, to some of the elaborate structures of the present day, historians Richard Veit and Mark Nonestied use grave markers to tell an off-beat account of New Jersey's history that is both fascinating and unique. In detailed descriptions, the authors explain what cemeteries and their gravemarkers say about different individuals.